2009
DOI: 10.1105/tpc.108.060525
|View full text |Cite
|
Sign up to set email alerts
|

The STRUCTURAL MAINTENANCE OF CHROMOSOMES 5/6 Complex Promotes Sister Chromatid Alignment and Homologous Recombination after DNA Damage inArabidopsis thaliana   

Abstract: Sister chromatids are often arranged as incompletely aligned entities in interphase nuclei of Arabidopsis thaliana. The STRUCTURAL MAINTENANCE OF CHROMOSOMES (SMC) 5/6 complex, together with cohesin, is involved in double-strand break (DSB) repair by sister chromatid recombination in yeasts and mammals. Here, we analyzed the function of genes in Arabidopsis. The wild-type allele of SMC5 is essential for seed development. Each of the two SMC6 homologs of Arabidopsis is required for efficient repair of DNA break… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
124
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(133 citation statements)
references
References 72 publications
(95 reference statements)
7
124
2
Order By: Relevance
“…Recently, a similar SMC5/6 complex, which also acts in DNA repair, was reported in plant cells (Watanabe et al, 2009). However, non-SMC components of this complex have not been characterized in terms of their interactions with the SMC5/6 complex.…”
Section: Arabidopsis Mms21 Is a Subunit Of The Smc5/6 Complexmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a similar SMC5/6 complex, which also acts in DNA repair, was reported in plant cells (Watanabe et al, 2009). However, non-SMC components of this complex have not been characterized in terms of their interactions with the SMC5/6 complex.…”
Section: Arabidopsis Mms21 Is a Subunit Of The Smc5/6 Complexmentioning
confidence: 99%
“…A previous study showed that heterozygotes for a transferred DNA insertion in the Arabidopsis SMC5 gene did not yield homozygous mutants and that siliques of heterozygous plants contained 25% shrunken seeds, indicating that SMC5 is essential for seed development (Watanabe et al, 2009). These findings prompted us to speculate that SMC5 might function in embryogenesis.…”
Section: Arabidopsis Mms21 Is a Subunit Of The Smc5/6 Complexmentioning
confidence: 99%
“…4 Similarly, mutations in the structural maintenance of chromosome 5/6 complex (SMC5/6) lead to defects in sister chromosome cohesion as well as impaired DNA repair in Arabidopsis. 27 All these data argue for a tight control between DNA replication, DNA repair and sister chromatid cohesion. As postreplicative DNA repair is impaired in bru1, 12 we need to further investigate this aspect in relation with GIPs and the nuclear periphery.…”
Section: Discussionmentioning
confidence: 99%
“…Representative gel images from at least three independent trials are shown for A, B, D, E, and F. A 1.59-kb AtPoll cDNA fragment was used as a probe in DNA and RNA gel blotting. (Dmitrieva and Burg, 2005;Watanabe et al, 2009). Therefore, we next specifically examined the induction pattern of AtPoll message levels, particularly in response to high salinity and MMC treatments, in 7-dold wild-type Arabidopsis seedlings.…”
Section: Abiotic and Genotoxic Stress Induces Atpoll Expressionmentioning
confidence: 99%